DUKUNGAN PSIKOLOGIS UNTUK PASIEN KANKER ANAK YANG KRITIS - Boas, Esther (Jurnal Biomedik : JBM, 2015)
Abstract: Regardless of age, malignant diseases and deaths can occur even in children. About 100 of one million children suffering from cancer every year. Indonesian laws do not allow the children to give any decision or refusal about the medical treatment directed to them. Moreover, there are posibilities that they do not get any information from the medical staff. The children know that something wrong is going to happen to them although their parents and doctors tell them nothing. Lack of information make them frightened and anxious. These feelings can give a long term impact if they finally being cured from their diseases. Medical staffs and family members have very important roles in giving the right information to the children concerning the current problem and the worst possibility, and also in giving physicological support.Keywords: dying child, cancer, communicationAbstrak: Kematian tidak memilih usia; anak-anak pun tidak luput dari kanker dan kematian. Sekitar 100 dari 1 juta anak terkena kanker setiap tahunya. Menurut undang-undang yang berlaku di Indonesia, anak-anak tidak diperbolehkan memberikan persetujuan atau penolakan atas tindakan kedokteran yang akan dilakukan padanya. Bahkan, informasi dari petugas kesehatan bisa saja tidak pernah mereka dengar. Anak-anak dapat mengetahui singkatnya harapan hidup mereka meskipun orangtua dan dokter tidak menceritakannya. Kurangnya informasi yang mereka dapatkan bisa menimbulkan rasa takut dan cemas, bahkan bisa berdampak panjang jika ternyata mereka dapat sembuh dari sakitnya. Tenaga medis dan keluarga berperan penting untuk memberikan informasi tentang masalah yang dihadapi, kemungkinan terburuk yang akan mereka hadapi, serta memberikan dukungan secara psikologis.Kata kunci: anak masa kritis, kanker, komunikasi